1988
DOI: 10.1007/bf00973296
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of brain and liver 3-hydroxy-3-methylglutaryl-CoA reductase and mevalonate-5-pyrophosphate decarboxylase in experimental hyperphenylalaninemia

Abstract: Experimental hyperphenylalaninemia has been induced in 5-day-old chicks by dietary treatments with phenylalanine and alpha-methylphenylalanine. An increase of nearly 8-fold in plasma Phe/Tyr ratio was found after 4 days of supplementation the standard diet with 5% phenylalanine plus 0.4% alpha-methylphenylalanine. The increase in this ratio was about 13-fold after 9 days of the same treatment. Similar results were observed in brain and liver, although the increases were smaller than those found in plasma. Tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
25
2
1

Year Published

1991
1991
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 28 publications
0
25
2
1
Order By: Relevance
“…These findings are in contrast to previous studies revealing lower serum cholesterol concentrations in patients with PKU [16], [17], [27], especially while under good metabolic control [18], and also compared to patients with a protein-restricted diet due to other inborn errors of amino acid metabolism [27]. Other studies showed a possible inhibition of cholesterol synthesis in vitro [31] and in animal models of PKU [32]. Colomé et al [27] detected an inverse correlation of phenylalanine and cholesterol concentrations in serum and hypothesized high plasma phenylalanine concentrations to inhibit cholesterol synthesis.…”
Section: Discussioncontrasting
confidence: 99%
“…These findings are in contrast to previous studies revealing lower serum cholesterol concentrations in patients with PKU [16], [17], [27], especially while under good metabolic control [18], and also compared to patients with a protein-restricted diet due to other inborn errors of amino acid metabolism [27]. Other studies showed a possible inhibition of cholesterol synthesis in vitro [31] and in animal models of PKU [32]. Colomé et al [27] detected an inverse correlation of phenylalanine and cholesterol concentrations in serum and hypothesized high plasma phenylalanine concentrations to inhibit cholesterol synthesis.…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, there are several regulatory mechanisms which contribute to cholesterol homeostasis. Although in this study we have only analyzed the blood lipid profile of patients with PKU, it is worth mentioning that an in vivo study, in which experimental hyperphenylalaninemia was induced in an animal model, demonstrated that there was an inhibition of two of the main regulatory enzymes of brain and liver cholesterogenesis: 3-hydroxy-3-methylglutaryl-CoA reductase and mevalonate-5-pyrophosphate decarboxylase [29]; and therefore a reduced cholesterol synthesis in the brain may indicate an association between impaired myelination and mental retardation in patients with PKU.…”
Section: Discussionmentioning
confidence: 99%
“…The cell culture medium of control cells was found to contain a residual level of Phe (278 mmol/L). However, this was below the level of Phe reported to inhibit either HMG-CoA reductase or MRC complex I-III activity and therefore it is unlikely that this basal level of Phe would be inhibitory to either MRC complex I activity or CoQ 10 synthesis (Castillo et al 1988;Rech et al 2002).…”
Section: Discussionmentioning
confidence: 95%
“…More specifically, squalene synthase has a lower affinity than trans-prenyl transferase for farnesyl pyrophosphate, so a reduction in the concentration of farnesyl pyrophosphate due to high Phe would be expected to have a less profound effect upon CoQ 10 synthesis than cholesterol synthesis (Faust et al 1980). Hence, although hyperphenylalaninaemia has been reported to inhibit cholesterol synthesis this would not necessarily result in a decrease in cellular CoQ 10 levels (Castillo et al 1988).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation